Calculus-based physics I - Schnick, Jeffrey W.; BC Open Textbook Project; BCcampus (Jeffrey W. Schnick, 2008)
"Calculus-Based Physics is an introductory physics textbook designed for use in the two-semester introductory physics course typically taken by science and engineering students."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Physics -- Textbooks; Electronic books